The impact of using Virtual laboratory applications inside the classroom on development academic achievement in science among eighth grade students - Alhosni, Omar Hamdan Salim (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to detect the impact of using virtual laboratory applications inside the classroom on academic achievement in science development among eighth grade students in shekh Said Harthy School. The study sample consisted of 60 male students in eighth grade. They were divided into two experimental groups of (30) students they were taught using virtual laboratory applications, and the number of (30) students they were taught using the traditional method. The research was based on a test of achievement test in scientific experiments as research tools. The research used the t-test to calculate the difference between the experimental and control groups, there are statistically significant differences at the level of significance (0.05) between the mean scores of the students of the experimental group were taught using virtual laboratory applications and the students of the control group were taught using traditional method, in the post achievement test for experimental group using (virtual laboratory). The study recommended working on guidance for the use and training of teachers on the use of virtual laboratory applications, and spreading awareness about its impact on the education development.
Keywords: Virtual Laboratories; Academic achievement; Scientific experiments; Science